Persona non grata a memoir of disenchantment with the Cuban revolution - Edwards, Jorge 1931-2023 (Paragon House, 1993)
In 1970 Jorge Edwards was sent by Chilean President Allende as his country's first envoy to break the diplomatic blockade that had sealed off Cuba for over a decade. His arrival coincided with the turning point of the Revolution, when Castro began to repress the very intellectuals he had once courted. A gifted writer, a diplomat, a socialist, an outsider, Edwards has a unique perspective on this crucial moment in history, which has determined Cuba's fate. As Jose Donoso has written, "Persona Non Grata reveals the essence of Castro's Cuba and Allende's Chile and offers a different view of what it means to be Latin American." In Kafkaesque detail, Edwards records the four explosive months he spent in Havana trying to open a Chilean embassy and his disenchantment with the Revolution